Conditional Populist Party Support The Role of Dissatisfaction and Incumbency - Wiesehomeier, Nina; Ruth Lovell, Saskia; Singer, Matthew (Cambridge University Press, 2025)
Populists emerge when distrust of state institutions or dissatisfaction with democracy convince voters that claims about conspiring elites blocking the general will are valid. We propose that these dynamics change when populists are incumbents; once they command institutions, their sustained support becomes contingent upon trust in the new institutional order, and they are held accountable for making people think democracy is working well. Newly collected data on party populism and survey data from Latin America show that support for populist parties in the region is conditioned by satisfaction with democracy as well as the incumbency status of populists. Dissatisfied voters support populist opposition parties, but support for populist incumbents is higher among those satisfied with democracy and its institutions. While democratic deficits and poor governance provide openings for populists, populists are held accountable for institutional outcomes.
Keywords: Populism; Incumbency; Democratic satisfaction; Accountability